2021
DOI: 10.3390/membranes11050366
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Chemical-Mechanical Ex Situ Aging on PFSA Membranes for Fuel Cells

Abstract: A proton-exchange membrane fuel cell (PEMFC) constitutes today one of the preferred technologies to promote hydrogen-based alternative energies. However, the large-scale deployment of PEMFCs is still hampered by insufficient durability and reliability. In particular, the degradation of the polyelectrolyte membrane, caused by harsh mechanical and chemical stresses experienced during fuel cell operation, has been identified as one of the main factors restricting the PEMFC lifetime. An innovative chemical-mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…It is speculated that more water molecules act as a good plasticizer at relatively higher humidity because the membranes gradually reduce their toughness and extend stress relaxation time [ 28 ]. It is also observed that the composite membrane Nafion XL ( Figure 3 ) takes much longer than Nafion 211 ( Figure 2 ) to reach 15% mechanical loss under the same blistering conditions, presumably due to the improved mechanical properties of Nafion XL, as shown in Table 1 [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is speculated that more water molecules act as a good plasticizer at relatively higher humidity because the membranes gradually reduce their toughness and extend stress relaxation time [ 28 ]. It is also observed that the composite membrane Nafion XL ( Figure 3 ) takes much longer than Nafion 211 ( Figure 2 ) to reach 15% mechanical loss under the same blistering conditions, presumably due to the improved mechanical properties of Nafion XL, as shown in Table 1 [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The AST (Figure 3) that was applied to the MEA was also designed to stress the membrane through humidity cycling and OCV hold sequences. As mentioned in the introduction, membrane aging mechanisms are governed by the mechanical and chemical stresses it undergoes during FC operation [ [41][42][43][44][45][46][47], and AST like this one ultimately lead to an increase of hydrogen crossover -evidenced for instance through the hydrogen permeation currents-and membrane failure [ 22,42 ]. In the present case, the AST was stopped before any noticeable increase of the hydrogen permeation current, but a significant thinning of membrane was however observed for the defective segments (Fig.…”
Section: Degradation Mechanismsmentioning
confidence: 99%
“…In addition to the CL, the membrane is also subjected to high mechanical and chemical stresses during FC operation [ [41][42][43][44][45][46][47]. The mechanical stresses are mainly due to humidity cycling, that causes the swelling and shrinking of the membrane following water-content variations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common membranes used in PEMFC are thin films of perfluorosulfonic acid copolymers (PFSA) such as Nafion®, with a proton conductivity approaching 0.1 S cm −1 in ideal conditions, a good chemical stability, and fast hydration dynamics 4,5 . These remarkable properties stem from both the superacidity of the ionic functions and their unique microstructure 6,7 .…”
Section: Introductionmentioning
confidence: 99%